2022
DOI: 10.1002/jmv.28201
|View full text |Cite
|
Sign up to set email alerts
|

Increased cases of influenza C virus in children and adults in Austria, 2022

Abstract: Sentinel surveillance of influenza‐like illnesses revealed an increase in the cases of influenza C virus in children and adults in Austria, 2022, compared to previous years, following one season (2020/2021), wherein no influenza C virus was detected. Whole‐genome sequencing revealed no obvious genetic basis for the increase. We propose that the reemergence is explained by waning immunity from lack of community exposure due to restrictions intended to limit severe acute respiratory syndrome coronavirus 2 spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…9 Collectively, these analyses indicate that RSV continued to circulate during the period of little or no observed incidence, and global surveillance did not detect the genetic ancestors leading to the diversification of RSV-B due to low incidence. As 2020-2022 represented a time of increased vigilance in diagnostic testing for respiratory viruses 14 we hypothesize that transmission was occurring at a low rate, with a similar molecular clock estimate as reported by others. 7,9,15 It is possible that this represents asymptomatic transmission, or could represent an unsampled population.…”
Section: Rsv Whole-genome Sequencing and Phylogenetic Analysissupporting
confidence: 79%
“…9 Collectively, these analyses indicate that RSV continued to circulate during the period of little or no observed incidence, and global surveillance did not detect the genetic ancestors leading to the diversification of RSV-B due to low incidence. As 2020-2022 represented a time of increased vigilance in diagnostic testing for respiratory viruses 14 we hypothesize that transmission was occurring at a low rate, with a similar molecular clock estimate as reported by others. 7,9,15 It is possible that this represents asymptomatic transmission, or could represent an unsampled population.…”
Section: Rsv Whole-genome Sequencing and Phylogenetic Analysissupporting
confidence: 79%
“…After the first case of SARS‐CoV‐2 infection was detected in February 2020, the frequency of influenza A and B viruses was appreciably reduced in Yokohama, Japan; however, the frequency of these viruses between January 2018 and December 2019 was 489 (36.7%) of 1331 respiratory specimens in this region [ 28 ]. In Australia between 2008 and 2014 [ 6 ], Austria between the 2016/2017 and 2021/2022 influenza seasons [ 7 ], Hong Kong between 2014 and 2019 [ 8 ], India between 2009 and 2015 [ 10 ], Spain between 2005 and 2012 [ 13 ], and the USA between 2006 and 2012 [ 14 ], the frequency of influenza C virus was 79 (0.6%) of 13,497, 108 (0.5%) of 22,565, 2394 (0.2%) of 1,088,090, 3 (0.1%) of 2530, 17 (0.6%) of 2687, and 13 (0.3%) of 4200 specimens, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Austria, influenza A and C viruses were not detected during the 2020/2021 season, and most cases diagnosed from sentinel samples were SARS‐CoV‐2; however, the frequency of influenza A and C viruses increased in the following 2021/2022 season [ 7 ]. The frequency of influenza C virus before the COVID‐19 pandemic was three (0.3%) of 1120, eight (0.4%) of 1952, four (0.1%) of 3278, and two (0.04%) of 4950 in the 2016/2017, 2017/2018, 2018/2019, and 2019/2020 seasons, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, they observed a significant proportion of patients with RSV infection who missed their first exposure. Furthermore, when comparing previous seasons, Campo and Redlberger-Fritz noted an increased number of Influenza C virus cases in Austria during 2022, and they concluded that this could likely be attributed to a decreased prevalence in prior seasons due to non-pharmaceutical interventions (NPIs) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%